Cognitive behavioral Therapy Based on Local Wisdom Culture to Increase Happiness and Slow Degradation of Cognitive Function in the Elderly Post-Stroke - Aristawati, Evy; Huda, Nurul; Dwi Cahyono, Bagus; Susanto, Tantut (Journal Of Nursing Practice, 2026)
Background: Stroke in the elderly often leads to physical, psychological, and quality of life deterioration, which can hinder post stroke rehabilitation. Although Cognitive Behavioural Therapy (CBT) has been widely applied, the use of Cognitive Behavioural Therapy (CBT) integrated with local wisdom remains limited, particularly among elderly stroke survivors. Purpose: This study aimed to explore the lived experiences of elderly individuals after stroke who received local wisdom based Cognitive Behavioural Therapy (CBT) using sulthon prayer as a therapeutic medium. Methods: This study employed a qualitative phenomenological design. A total of 25 elderly post stroke participants were selected through purposive sampling and participated in in depth interviews. Data were analysed using thematic analysis following Braun and Clarke’s approach. Results: The findings revealed three main themes, namely biological experiences, psychosocial experiences, and spiritual experiences, reflecting participants’ perceptions of physical comfort, emotional regulation, and enhanced spiritual meaning during the recovery process. In conclusion, local wisdom based Cognitive Behavioural Therapy (CBT) using sulthon prayer provides meaningful biological, psychosocial, and spiritual support for elderly individuals after stroke. Conclusions: These findings imply that integrating culturally and spiritually sensitive Cognitive Behavioural Therapy (CBT) interventions may enhance holistic nursing care and rehabilitation outcomes for elderly stroke survivors.